Effect of electrical stimulation combined with graphene-oxide-based membranes on neural stem cell proliferation and differentiation. Issue 1 (4th December 2019) - Fu, Chuan; Pan, Su; Ma, Yue; Kong, Weijian; Qi, Zhiping; Yang, Xiaoyu
Abstract: The combination of composite nerve materials prepared using degradable polymer materials with biological or physical factors has received extensive attention as a means to treat nerve injuries. This study focused on the potential application of graphene oxide (GO) composite conductive materials combined with electrical stimulation (ES) in nerve repair. A conductive poly(L-lactic-co-glycolic acid) (PLGA)/GO composite membrane was prepared, and its properties were tested using a scanning electron microscope (SEM), a contact angle meter, and a mechanical tester. Next, neural stem cells (NSCs) were planted on the PLGA/GO conductive composite membrane and ES was applied. NSC proliferation and differentiation and neurite elongation were observed using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, immunofluorescence, and PCR, respectively. The results showed that the PLGA/GO membrane had good hydrophilicity, mechanical strength, and protein adsorption. ES combined with the PLGA/GO membrane significantly promoted NSC proliferation and neuronal differentiation on the material surface and promoted significant neurite elongation. Our results suggest that ES combined with GO-related conductive composite materials can be used as a new therapeutic combination to treat nerve injuries.